M14 Understanding and improving participants' experience of health research; patient evaluation of research participation in a dedicated respiratory biomedical research unit (bru) clinical research facility (crf). (15th November 2017) - Dobra, R; Guilmant, E; Higgins, T; Fleming, S
Abstract : Background: It is increasingly recognised that incorporating patients' views in trial development improves feasibility, satisfaction and efficiency in health research. To date, there is little research on the impact of institutional organisational factors on patients' research experiences. Aims: To examine how organisational factors in our respiratory CRF impact on the research experience for patients, and to understand the factors influencing recruitment, retention and satisfaction. Through understanding these, we hope to incorporate patients' views into trial implementation at our site, and suggest elements that may be transferable to other centres. Methods: A researcher independent from the CRF conducted semi-structured interviews. Patients were invited to participate on completion of one of three projects, selected to encompass different trial designs and include features previously proposed as controversial or challenging aspects of participation. A purposive, non-stratified cohort was used. Interviews were recorded, transcribed and analysed by constant comparative approach. Results: 25 subjects were interviewed; 17 with COPD, 4 OSA and 4 healthy volunteers. 16% had received their diagnosis within a week of parent-trial enrolment. 20% work fulltime. Patient satisfaction was high, although those newly diagnosed at parent-trial enrolment tended towards lower satisfaction and perceived their role differently. Factors motivating recruitment and retention were numerous and interlocked. Only four patients participated expecting direct health benefits. Communication, appointment flexibility and respect for time outweighed the effects of pain, fatigue and anxiety in patient retention. Social benefits of participation and feeling like a team player were important. The dedicated research facility made patients feel safer and the project was valued. Payment for participation was controversial. Reimbursement of expenses was necessary for our predominantly retired population. Transport provision was vital to breathless patients. Participation negatively impacted health perception for some. Conclusions: An appreciation of how participants perceive their role may aid targeting recruitment strategies. Staff must recognise that valuing patients' time and making them feel like an integral team-player improves satisfaction and retention. Researchers should consider transport provision, appointment flexibility, physical environment and reimbursing expenses when resourcing trials. Healthcare professionals should be sensitive to the impact of trial participation on health-perception, particularly for those with progressive disease.